Ultraviolet and blue cathodoluminescence from cubic Y2O3 and Y2O3:Eu3+ generated in a transmission electron microscope. Issue 29 (8th July 2016) - den Engelsen, D.; Fern, G. R.; Ireland, T. G.; Harris, P. G.; Hobson, P. R.; Lipman, A.; Dhillon, R.; Marsh, P. J.; Silver, J.
Abstract : The investigation of cubic spherical submicron particles of non-doped Y2 O3 and Y2 O3 doped with Eu 3+ in a TEM using CL from individual particles is described. Abstract : Herein we describe the investigation of cubic spherical submicron particles of non-doped Y2 O3 and Y2 O3 doped with Eu 3+ in a transmission electron microscope (TEM) equipped with a spectrometer to detect cathodoluminescence from individual particles. Each submicron particle was made up of nanometre sized crystals. We found that these crystals showed a broad emission band at 353 nm upon bombardment with 200 keV or 80 keV electrons. Upon increasing the Eu 3+ concentration from 0 to 2 mol% this UV/blue emission was gradually quenched: at Eu 3+ concentrations >2 mol% no UV/blue emission was detected, only the well-known cathodoluminescence (CL) spectrum of Y2 O3 :Eu 3+ could be recorded. This UV/blue emission has been attributed to the intrinsic luminescence of Y2 O3 caused by self-trapped excitons. We found that the UV/blue luminescence was strongly temperature dependent and that the trap depth of the self-trapped excitons was 0.14 eV. The ratios of the spectral radiances of 5 D1 → 7 F J and 5 D0 → 7 F J ( J = 0, 1…6) Eu 3+ transitions in the CL-TEM spectra of Y2 O3 :Eu 3+ at low Eu 3+ concentrations was about a factor of 10 larger than those recorded at 15 keV. This phenomenon has been explained by absorption of the intrinsic luminescence of Y2 O3 by Eu 3+ .